Influencer Traits and Information Credibility in Driving Gen Z Women’s Purchase Intentions - P, Vinish; Hawaldar, Iqbal Thonse; Soni, Aditi; Khan, Roohi Kursheed; Pinto, Prakash (International Journal of Accounting and Economics Studies, 2025)
Influencer marketing has evolved from a hobby into a key business strategy, as companies increasingly collaborate with influencers to ‎promote their products. This shift is especially impactful for Generation Z, who rely heavily on social media to discover and follow the ‎latest fashion and lifestyle trends. This study examines how YouTubers' influencer marketing impacts the credibility of information and ‎influences purchasing decisions for cosmetic brands. Using a descriptive study design, 385 digitally active Gen Z participants were ‎selected through snowball sampling, highlighting their significant role in shaping consumer trends. The study utilised Confirmatory ‎Factor Analysis (CFA) to assess reliability and validity, while hypotheses were tested using Structural Equation Modelling (SEM). The ‎study found that source-related factors like expertise (β= 0.216), trustworthiness (β=0.678), likability (β=0.287), and homophily ‎‎(β=0.298) positively and significantly influence perceived information credibility. However, platform factors like social advocacy and ‎interactivity had no significant impact, while argument quality negatively influenced information quality. Ultimately, perceived information credibility significantly influences purchase intentions (β=0.564) for beauty products among Generation Z women in India. The ‎study's results are in partial agreement with previous research, shedding light on how Generation Z women engage with social media ‎content when seeking recommendations for beauty products‎.
Keywords: Generation Z; India; Purchase Intention; Social Media; YouTube Influencers